Travelers as sentinels for Chikungunya Fever, Brazil - Chaves, Tânia do Socorro Souza (2012)
University of São Paulo. School of Medicine. São Paulo, SP, Brazil / Emílio Ribas Institute of Infectious Diseases. São Paulo, SP, Brazil.